Building clinically relevant outcomes across the Alzheimer's disease spectrum. Issue 1 (26th June 2021) - Rentz, Dorene M.; Wessels, Alette M.; Annapragada, Ananth V.; Berger, Anna‐Karin; Edgar, Chris J.; Gold, Michael; Miller, David S.; Randolph, Christopher; Ryan, J. Michael; Wunderlich, Glen; Zoschg, Megan Canniere; Trépel, Dominic; et al.
Abstract: Demonstrating that treatments are clinically meaningful across the Alzheimer's disease (AD) continuum is critical for meeting our goals of accelerating a cure by 2025. While this topic has been a focus of several Alzheimer's Association Research Roundtable (AARR) meetings, there remains no consensus as to what constitutes a "clinically meaningful outcome" in the eyes of patients, clinicians, care partners, policymakers, payers, and regulatory bodies. Furthermore, the field has not come to agreement as to what constitutes a clinically meaningful treatment effect at each stage of disease severity. The AARR meeting on November 19–20, 2019, reviewed current approaches to defining clinical meaningfulness from various perspectives including those of patients and care partners, clinicians, regulators, health economists, and public policymakers. Participants discussed approaches that may confer clinical relevance at each stage of the disease continuum and fostered discussion about what should guide us in the future.